A Distributed Approach for Disk Defragmentation (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Fragmentation is a computing problem that occurs when files of a computer system are replaced frequently. In this paper, the fragments of each file are collected and grouped, thanks to ant-colony optimization ACO, in one place as a mission for a group of ants. The study shows the ability of ants to work in a distributed environment such as cloud computing systems to solve such problem.  The model is simulated using NetLogo.